DOSE RATE IN A DEACTIVATED URANIUM MINE - Wagner De Souza Pereira; Alphonse Kelecom; Ademir Xavier da Silva; José Marquez Lopes; Alessander Sá do Carmo; Ayandra Oliveira Dias; Carlos Eduardo Cogo Pinto (Brazilian Journal of Radiation Sciences)
The Ore Treatment Unit is a deactivated uranium mine and milling situated in Caldas, MG, BR. Although disabled, there are still areas considered controlled and supervised from the radiological point of view. In these areas, it is necessary to keep an occupational monitoring program to ensure the workers' safety and to prevent the dispersion of radioactive material. For area monitoring, the dose rate, in µSv∙h-1, was measured with Geiger Müller (GM) area monitors or personal electronic monitors type GM and thermoluminescence dosimetry (TLD), in mSv∙month-1, along the years 2013 to 2016. For area monitoring, 577 samples were recorded; for personal dosimeters monitoring, 2,656; and for TLD monitoring type, 5,657. The area monitoring showed a mean dose rate of 6.42 µSv∙h-1 associated to a standard deviation of 48 µSv∙h-1 with a maximum recorded value of 685 µSv∙h-1. 96 % of the samples were below the derived limit per hour for workers (10 µSv∙h-1). For the personal electronic monitoring, the average of the data sampled was 15.86 µSv∙h-1, associated to a standard deviation of 61.74 µSv∙h-1. 80 % of the samples were below the derived limit and the maximum recorded was 1,220 µSv∙h-1. Finally, the TLD showed a mean of 0.01 mSv∙h-1 (TLD detection limit is 0.2 mSv∙month-1 equivalent to 0.28 µSv∙h-1), associated to a standard deviation of 0.08 mSv∙h-1. 98% of the registered values were below 0.2 mSv∙month-1 and less than 2 % of the measurements had values above the limit of detection. The samples show areas with low risk of external exposure, as can be seen by the TLD evaluation. Specific areas with greater risk of contamination have already been identified, as well as operations at higher risks. In these cases, the use of the individual electronic dosimeter is justified for a more effective monitoring. Radioprotection identified all risks and was able to extend individual electronic monitoring to all risk operations, even with the use of the TLD.